(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Major depressive disorder is one of the public health problems with prevalence among worldwide. Major Depression (MD) is the most prevalent comorbid mood disorder in eating disorder (ED) patients, and the severity of depressive symptomatology seems to be related to the ED. Most international clinical practice guidelines recommend psycho-educational intervention as first step in the treatment protocol. This study aimed to find out the effect of the psycho-educational program as the treatment of choice for depression patient with eating disorder. Methods: A quantitative quasi experimental study with pre-post intervention design used to evaluate the effectiveness of psychoeducation program. A non-probability, purposive sample size of (50) patients with major depressive disorder were recruited to the study from January 10th 2018 till October 1st 2019. Beck depression inventory (BDI) was used for measuring the severity of depression, and Garner eating disorder inventory (G-EDI) was other measure used to assess eating behavior problems. Data of the present study was analyzed through using application of statistical package for social sciences (SPSS) version. Results: The study indicated a significant difference in Beck depression score in intervention and control group after intervention (P< 0.001). It shows that the mean ranks of the difference (gain in scores) of the experimental group was significantly (p < 0.05) higher than the mean ranks of the difference of the control group for all the parameters of eating disorders. Conclusion: The findings indicated that the 6-sessions psycho-education program has great impact on the severity of depression and all component of eating disorder in patient diagnosed with depression in associated with eating disorder